Efeitos do treinamento intervalado de alta intensidade em parâmetros reprodutivos de ratos adultos espontaneamente hipertensos - Oliveira, Margarete Jardinetti (2020)
Hypertension is one of the causes of low fertility in men, as it reduces the production of testosterone and spermatogenesis. Physical exercises are indicated for lowering blood pressure and improving the individual's general health. The thesis consists of a review on the effects of high-intensity interval training on reproductive parameters of spontaneously hypertensive adult rats and an article on an experimental work carried out through high-intensity interval training that modulates the effects of hypertension on sperm parameters in adult rats spontaneously hypertensive. The aim of the present study was to evaluate reproductive parameters of spontaneously hypertensive rats (SHR) submitted to high-intensity interval training (HIIT). 24 rats were used, divided into three groups: WKY (control group Wistar-Kyoto rats, sedentary normotensive, n = 5); SHR (SHR rat group, n = 9); and SHR HIIT (group of SHR rats submitted to HIIT, n = 10). HIIT was performed on a treadmill for 5 days a week for 8 weeks, for approximately 50 minutes, based on maximum exhaustion speed, with rest intervals. The training protocol consisted of 5 minutes of warm-up at 60% of the maximum speed of exhaustion, and after warm-up, the training was 4 minutes at 100% of the maximum speed achieved in the exhaustion test, followed by 3 minutes at 60% of the maximum exhaustion speed, which was repeated 5 times in the first week, six times in the second and third weeks and from the fourth to the eighth week repeated each session seven times, with the maximum exhaustion speed being adjusted before starting the fifth week and in the last two weeks of training. After euthanasia, the reproductive organs and sperm were harvested. All data were tested by ANOVA followed by Tukey, except for data from testicular cells that were subjected to the Kruskal-Wallis test, followed by Dunn (P <0.05). The SHR group had a lower percentage of mobile sperm with a progressive trajectory (P <0.05) and a higher number of immobile sperm than other groups, WKY and SHR-HIIT. There was no significant difference between groups in sperm morphology or in the diameter of seminiferous epithelium. The SHR-HIIT group had a higher number of germ cells and Sertoli cells. SHR had less gene expression of angiogenic factors Vegf, Flt-1, Kdr and hypoxia-inducing factor (Hif-1α). We concluded that HIIT for two months restores the sperm motility of hypertensive rats and the number of germ cells and Sertoli cells and that hypertension decreases the relative gene expression of angiogenic factors.